Violence against physicians and nurses in a hospital: How does it happen? A mixed-methods study - Sigal Shafran-Tikva; David Chinitz; Zvi Stern; Paula Feder-Bubis (BMC, 2017)
Abstract Background Violence against medical personnel is unexpected in hospitals which are devoted to healing, and yet, it is frequent and of concern in the health system. Little is known about the factors that lead to hospital violence, and even less is known about the interactions among these factors. The aim of the study was to identify and describe the perceptions of staff and patients regarding the factors that lead to violence on the part of patients and those accompanying them. Methods A mixed-methods study in a large, general, university tertiary hospital. A self-administered survey yielding 678 completed questionnaires, comprising 34% nurses and 66% physicians (93% response rate). Eighteen in-depth interviews were conducted separately with both victims and perpetrators of violent episodes, and four focus-groups (N = 20) were undertaken separately with physicians, staff nurses, head-nurses, and security personnel. Results Violence erupts as a result of interacting factors encompassing staff behavior, patient behavior, hospital setting, professional roles, and waiting times. Patients and staff reported similar perceptions and emotions regarding the episodes of violence in which they were involved. Of 4,047 statements elicited in the staff survey regarding the eruption of violence, 39% referred to staff behavior; 26 % to patient/visitor behavior; 17% to organizational conditions, and 10% to waiting times. In addition, 35% of the staff respondents reported that their own behavior contributed to the creation of the most severe violent episode in which they were involved, and 48% stated that staff behavior contributed to violent episodes. Half of the reasons stated by physicians and nurses for violence eruption were related to patient dissatisfaction with the quality of service, the degree of staff professionalism, or an unacceptable comment of a staff member. In addition, data from the focus groups pointed to lack of understanding of the hospital system on the part of patients, together with poor communication between patients and providers and expectations gaps. Conclusions Our various and triangulated data sources show that staff and patients share conditions of overload, pressure, fatigue, and frustration. Staff also expressed lack of coping tools to prevent violence. Self-conscious awareness regarding potential interacting factors can be used to develop interventions aimed at prevention of and better coping with hospital violence for both health systems' users and providers.